2019
DOI: 10.1186/s41927-019-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted impact of anxiety and depression on patients with rheumatoid arthritis

Abstract: BackgroundThe prevalence of mood disturbances such as anxiety and depression is greater in rheumatoid arthritis (RA) patients than in the general population. Given this association, the primary aim of this study was to assess the incremental impact of anxiety or depression on patients with RA from the United States of America (USA) and Europe, independent of the impact of the underlying RA disease.MethodsRheumatologists (n = 408) from the USA and 5 European countries completed patient record forms for a predet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
(38 reference statements)
2
35
0
1
Order By: Relevance
“…Depression and anxiety are frequently observed in rheumatoid arthritis or lupus erythematosus patients. [32][33][34][35] The current health crisis brought about by the quick spread of the SARS-Cov2 virus is a challenge to everyone's physical and mental health. In a pandemic such as this, fear increases anxiety and stress levels in healthy individuals and intensifies the symptoms of those with pre-existing psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression and anxiety are frequently observed in rheumatoid arthritis or lupus erythematosus patients. [32][33][34][35] The current health crisis brought about by the quick spread of the SARS-Cov2 virus is a challenge to everyone's physical and mental health. In a pandemic such as this, fear increases anxiety and stress levels in healthy individuals and intensifies the symptoms of those with pre-existing psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of scores was based on previous studies. 14,15,22 The total depression subscale was divided into normal (0-9), mild depression (10)(11)(12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21-27) and extremely severe depression symptoms (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The total anxiety subscale score was divided into normal (0-6), mild anxiety (7-9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19) and extremely severe anxiety symptoms (20-42).…”
Section: Measures and Outcomesmentioning
confidence: 99%
“…These studies usually reflect the real situation of patients by self‐reported questionnaires and scales for evaluation. Although there are differences between the outcomes reported by patients and medical staff (Peterson et al., 2019), the results from patients are still valuable original data, providing convenience for the development of clinical research and various clues for further research. Ramos et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and physicians report anxiety and depression differently. One thousand fifteen pairs of RA patients and their physicians completed the anxiety/depression questionnaires; 38.4%, 9.9% and 67.1% cases of anxiety/depression were reported by the patients only, physicians only and both patients and physicians respectively [23].…”
Section: The Patients' Viewmentioning
confidence: 99%